Application of Health Belief Model (HBM) on Sexual Behavior in Teens in Senior High School 3 Pasundan Cimahi : Adolescents, Health Belief Model (HBM), Sexual Behavior - Fifi Siti Fauziah; Dwi Hastuti (STIKep PPNI Jawa Barat, 2021)
Adolescent growth and development is a process or stage of change or transition from childhood to adulthood marked by various changes, including physical changes. One of the prominent characteristics of the physical changes in the active operation of the sex glands is a sexual urge. Adolescent sexual behaviour can also have psychological and social impacts. To avoid unhealthy sexual behaviour, efforts are made to prevent adolescent sexual behaviour that can be done internally and externally. Internally, the factor that plays an important role for adolescents in preventing sexual behaviour is self-control. The self-control factors can be studied with Health Belief Model (HBM) approach using a psychological model to predict the causes of healthy behaviour. This research method is a quantitative research using a quasi-experimental research with the type of design one group pre and post intervention. The results showed that sexual behavior before the implementation of HBM was unhealthy with a median value of 1, after the implementation of HBM, adolescent sexual behavior was healthy with a median value of 0. This indicates that there is a relationship between the application of HBM and adolescent sexual behavior in SMK Pasundan 1 Cimahi with p-value 0.002. The application of HBM can reduce unhealthy sexual behavior as a guide for adolescents in increasing knowledge, providing information to increase understanding of healthy sexual behavior.